Pembentukan Karakter Religius Peserta Didik melalui Pembiasaan Shalat Dhuha UPTD SMP Negeri 1 Kecamatan Harau - Yulianti, Fadila; Wardefi, Riza (TSAQOFAH, 2025)
This study discusses the development of religious character through the practice of Dhuha prayer at UPTD SMP Negeri 1 Kecamatan Harau. The purpose of this research is to examine the implementation of Dhuha prayer activities as a means of fostering students’ religious character and to identify supporting and inhibiting factors in its implementation. The method used is qualitative with a descriptive approach. Data sources include informants such as the principal, vice principal, Islamic Religious Education (PAI) coordinator, Dhuha prayer supervising teacher, and ten seventh-grade students. Data collection techniques included observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was tested using technique and source triangulation. The findings show that the implementation of Dhuha prayer habituation at the school is well-executed and has significantly contributed to the development of students’ religious character. The activity has proven effective in fostering discipline, honesty, and responsibility, enhancing worship awareness, strengthening faith and devotion to Allah SWT, and promoting mutual respect among people of different religions. Supporting factors include school support, teacher involvement, and adequate facilities and infrastructure. Meanwhile, inhibiting factors involve a lack of awareness among some students and technical challenges in maintaining the routine. The conclusion of this study is that Dhuha prayer habituation is an effective strategy for holistically shaping students' religious character within the school environment.